The Relationship of Green Logistics and Green Manufacturing to Supply Chain Sustainability - Candrarahayu, Anisa Mahadita; Kuncoro, Engkos Achmad; Nofrisel, (Langit Biru: Jurnal Ilmiah Aviasi, 2025)
This study explores the impact of Green Logistics and Green Manufacturing on Supply Chain Sustainability in the Deltamas Industrial Area, Bekasi, Indonesia. The research highlights the growing importance of sustainable practices in supply chains to reduce environmental impacts such as emissions and waste. Data were collected through surveys, Focus Group Discussions (FGD), and expert interviews with company managers, government representatives, and industry professionals. The findings, analyzed using Structural Equation Modeling (SEM), reveal that both Green Logistics and Green Manufacturing significantly positively influence Supply Chain Sustainability. These results align with qualitative insights from experts, which emphasize the importance of green practices in reducing carbon footprints, enhancing operational efficiency, and improving corporate image. The study concludes that implementing Green Logistics and Green Manufacturing in the industrial sector is essential for achieving sustainable supply chain goals.